(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The research aimed to reveal the degree to which social studies teachers possess the digital skills of the twenty-first century teacher, and to measure the differences between the scores of the teachers’ answers to the digital skills of the twenty-first century teacher questionnaire according to the variables: (gender, number of years of experience, academic qualification). The research relied on the descriptive analytical method, and the research was applied to a sample of (358) male and female general social studies teachers in the city of Damascus. A questionnaire was applied for the digital skills of the twenty-first century teacher, which consisted of (80) items. Among the most important findings of the research: The degree to which social studies teachers in Damascus possess the digital skills of the twenty-first century teacher was high, as the rank arithmetic mean of the response of the research sample members reached (3.51). There are no statistically significant differences between the average scores of the research sample’s responses to the digital skills questionnaire for the twenty-first century teacher according to the variables: (gender, number of years of experience). There are differences in the scores of the research sample members’ responses to the twenty-first century teacher’s digital skills questionnaire according to the academic qualification variable in favor of teachers who hold an academic qualification (diploma or higher).